Kingship and colonialism in India's Deccan, 1850-1948 - Cohen, Benjamin B. (Palgrave Macmillan, 2007)
Rejecting simplified notions of 'civilizational clashes', this book argues for a new perspective on Hindu, Muslim, and colonial power relations in India. Using archival sources from London, Delhi, and Hyderabad, the book makes use of interviews, private family records and princely-colonial records uncovered outside of the archival repositories.